Epidemiology of Poisonings in Shahid Beheshti Hospital in Kashan, Iran - Dehghani, R; Fathi, B; Aboo-Saaidi, Z; Jalalati, A; Ramezani, M; Nohi, M (International Journal of Medical Toxicology and Forensic Medicine, 2015)
Background: Poisoning is a major public health problem and is one of the most common causes of referral to emergency departments. The aim of this study was to evaluate and define clinical and demographic details of poisoned patients who were admitted to Shahid Beheshti Hospital, Kashan, Iran in 2010. Methods: In this descriptive-analytical and retrospective study, necessary data were collected from medical records of admitted poisoned patients and were evaluated prospectively and statistically analyzed and presented in the form of tables and graphs. Results: Of 163 poisoned patients in this study, 47.6% were females and 52.4% were male. 88% of patients were from urban areas and the rest from rural areas. The most common reason of poisoning was suicide 50.6%, while 38.1% were accidental, and 11.3% had a variety of different reasons. Age group of 0-10 years was the most predominant affected group with 26.8% poisoned patients. The most common poisoning agents were clonazepam, acetaminophen, diazepam and methadone. Four patients in the study population died (2.4%). Conclusion: The medications are the leading causes of poisoning, especially in children. Therefore, parents are advised to keep the medicines correctly, out of sight and reach of children, read the label carefully; learn about their safety and the right way of their use. It is also recommended to immediately dispatch the poisoned child to the emergency department. Giving the crucial information about the poisoning to help the medical staff to treat the child effectively and quickly, reduce the hospitalization period, and possibility of child death.